Peraturan Daerah No 9 Tahun 2016 Tentang Penataan Organisasi Perangkat Daerah Pemerintah Provinsi Jawa Tengah - Gumilar Eka Saputra; Susilo Utomo . (Journal of Politic and Government Studies, 2017)
Implementation of regional autonomy (decentralization) is an effort to improve the performance of governance in the region both in the legislature (DPRD) and executive (head area), and also the local bureaucracy, each district / city has full authority to formulate policies, vision, mission and program development closer to the needs and desires of each region. Such changes in a system formed by the central government to the regions will affect the working system, payroll system, budget, administration, scope of work and so that the settings will be adjusted to the policy of strategic stats and abilities that exist in each area. This makes each region should establish, or even to readjust the system bureaucratic work in the area to fit the character of their respective regions to create regional administration in accordance with strategic planning and the ability of each area Government formed to carry out efforts in achieving the objectives of the state, in accordance with the will to be achieved by all the people, which includes order, ensure fairness, doing public works, improve welfare, and preservation of natural resources and the environment. In order to achieve that all governments need to operationalize the organ executing the duties of government in real terms in the lives of everyday people, Organ executor is called bureaucracy. Therefore, the realm of political science, known as a bureaucratic state machine (state machinery) in charge to realize the will of the people is ideal. This the bureaucracy is a tool of the government in creating a governance process in order to achieve the goal, and in order for their objectives to the social order. Therefore the government should look again whether the working system (organization) has been running effectively and efficiently, or should be done restructuring of (reform of the bureaucracy) to fit the dynamic conditions in the community. Reform of the bureaucracy is essentially a change effort or arrangement made conscious government in order to adjust the apparatus of government or government agency with the dynamic changes that occur in a dynamic environment in the community. Efforts are made to carry out the roles and functions correctly and consistently, in order to produce a benefit as mandated by the constitution. Bureaucratic reform should have a goal or objective meaning for improvement of good governance, objectives to be achieved. The targets include, first a lack of compatibility between the number and composition of employees with the needs of the work unit has been arranged based on the vision and mission so that employees have clarity and responsibility. Second, the creation of a match between the competences of the employees with terms of office.Third, the proportional distribution of employees in each unit of work in accordance with their respective workloads. Fourth, the institutional structure of the bureaucracy should see the layout rules (constitutional) that already exist. Parson in HM Ismail explained that the reorganization of the government organization can be reached in two ways, namely downsizing and rightsizing. Downsizing is necessary for improved efficiency in government, because government organizations large and has not been good fat and less efficient. Downsizing meant that government organizations can be made more streamlined and less bureaucratic. Rightsizing needed so that the size of government organizations that there is absolutely appropriate to the needs and conditions. So in addition to downsizing also need to consider the needs of the implications for the size of the organization, and most importantly is to adjust the organizational structure in various areas with the competence of institutions and personnel available. Keywords:Decentralization, Bureaucracy, Bureaucracy Reform